PERFORMANCE IMPROVEMENT MODEL FOR CULINARY BUSINESS IN TASIKMALAYA - Irman Firmansyah; Nisa Noor Wahid; Adil Ridlo Fadillah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
This study aims to solve the problems that occur in the culinary business in Tasikmalaya which is currently easy to go out of business. Therefore it is necessary to find a useful model to solve the problem through testing the ability to prepare financial statements and managerial ability in improving the performance of SMEs/MSMEs, especially on culinary business in Tasikmalaya. Through the research will be known the influence of the ability to prepare financial statements and managerial ability on performance, so that in the short term management will know how the benefits obtained if culinary entrepreneurs are ability to prepare financial statements well and improve managerial ability. The method used is through survey and analyzed using regression model through multiple regression analysis with the help of Smart PLS. The results showed that the ability to prepare financial statements has a positive effect on the performance of culinary business in Tasikmalaya City, managerial ability does not affect the performance of culinary business in Tasikmalaya City. Thus culinary business owners need the ability to prepare financial statements so that entrepreneurs are able to analyze the condition of their business through information generated from the financial statements.Keywords: ability to prepare financial statements, managerial ability, performance